2012
DOI: 10.7326/0003-4819-157-1-201207030-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Pharmacist Intervention on Clinically Important Medication Errors After Hospital Discharge

Abstract: Background Clinically important medication errors are common after hospital discharge. They include preventable or ameliorable adverse drug events as well as medication discrepancies or non-adherence with high potential for future harm (potential adverse drug events). Objective The Pharmacist Intervention for Low Literacy in Cardiovascular Disease (PILL-CVD) study sought to determine the effect of a tailored intervention on the occurrence of clinically important medication errors after hospital discharge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
299
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 279 publications
(317 citation statements)
references
References 29 publications
6
299
2
1
Order By: Relevance
“…[23][24][25] However, while the nurse-reviewers were not blinded to urban/ rural status, they used a structured interview guide and patient summary process. 15,16 Furthermore, physician-adjudicators were blinded to residence status, rigorously trained, and with co-adjudication by two physicians (and a third if necessary). Lastly, recall bias was addressed by corroborating all patient reports to the health record.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[23][24][25] However, while the nurse-reviewers were not blinded to urban/ rural status, they used a structured interview guide and patient summary process. 15,16 Furthermore, physician-adjudicators were blinded to residence status, rigorously trained, and with co-adjudication by two physicians (and a third if necessary). Lastly, recall bias was addressed by corroborating all patient reports to the health record.…”
Section: Discussionmentioning
confidence: 99%
“…The third component consisted of a full review of organ systems, with questions addressing issues such as fever, pain or discomfort, inability to eat, nausea or vomiting, diarrhea, shortness of breath, cough, skin breakdown, rash, falls, swollen legs, urinary frequency, and dysuria. 2,3,15,16 If patients answered that any of these symptoms were new or worse since discharge, the nurse-reviewer asked additional follow-up questions regarding the severity of the symptoms, the timing of symptoms in relation to hospitalization and treatments, and the resolution of symptoms, in order to determine the relationship between these symptoms and health care delivery.…”
Section: Telephone Interviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, medication discrepancies after hospital discharge pose safety risks. [21][22][23] Although inpatient nurses may review discharge medications, it is the primary care nurse who can reconcile the discharge medication list with the prehospitalization medication list and identify discrepancies. The outpatient nurse has easier access to the PCP to address discrepancies.…”
Section: After Hospital Dischargementioning
confidence: 99%
“…One study found that 81% of patients requiring assistance with basic functional needs failed to receive a home care referral, and 65 percent said no one at the hospital talked to them about managing their care at home [1] . A 2012 study published in the Annals of Internal Medicine [2] found that patients were frequently taking medications too long, missing doses, or taking the wrong dose. Twenty-three percent of these errors were found to be serious and 1.8% were life-threatening.…”
Section: Introductionmentioning
confidence: 99%